2015
DOI: 10.26577/2218-7979-2015-8-2-13-17
|View full text |Cite
|
Sign up to set email alerts
|

Сhemical composition of polysaccharides from wheat cell culture

Abstract: Polysaccharides were extracted from wheat suspension culture and cultivated cells. Gaz-liquid chromatography of wheat suspension culture allowed identifying the composition of polysaccharides that were found to contain arabinose, xylose, galactose, glucose, and a little amount of mannose and rhamnose. In dried cultivated cells the polysaccharide structure consisted mainly from arabinose, xylose, and galactose. It was found that the percentage of the amount of monosaccharides was positively correlated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our previous research enabled us to identify bioactive polysaccharides in cereal cell suspension cultures [ 30 ]. We explored the chemical composition and physical properties of these wheat PSs, which were found to be represented by arabinogalactans and supposed to be represented by xyloglucans, arabinoxylans, and glucans, according to their monosaccharide composition [ 31 , 32 ]. In addition, we showed that monosaccharide composition changed significantly depending on the cultivation media [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research enabled us to identify bioactive polysaccharides in cereal cell suspension cultures [ 30 ]. We explored the chemical composition and physical properties of these wheat PSs, which were found to be represented by arabinogalactans and supposed to be represented by xyloglucans, arabinoxylans, and glucans, according to their monosaccharide composition [ 31 , 32 ]. In addition, we showed that monosaccharide composition changed significantly depending on the cultivation media [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that phytohormones in tissue culture are widely used to enhance or change the biosynthesis of metabolites [13]. Recent studies have shown that auxins are able to enhance susceptibility to bacterial invasion [14] and induce upregulation of biosynthetic genes [15]. It was reported that abscisic acid is capable of altering cell wall properties and compositions [16].…”
Section: Introductionmentioning
confidence: 99%